Callable Russian Options and Their Optimal Boundaries. (24th May 2009) - Suzuki, Atsuo; Sawaki, Katsushige
Abstract : We deal with the pricing of callable Russian options. A callable Russian option is a contract in which both of the seller and the buyer have the rights to cancel and to exercise at any time, respectively. The pricing of such an option can be formulated as an optimal stopping problem between the seller and the buyer, and is analyzed as Dynkin game. We derive the value function of callable Russian options and their optimal boundaries.